Histopathologic Examination of Ovarian Lesions: A Prospective Observational Study in Women from Central India - Somya Saxena; Rajender Singh; Harshul Patidar; Ringku Bhagora; Vivek Khare (Clinical and Research Journal in Internal Medicine, 2023)
Background: There is age related increase in the incidence of ovarian cancer. Most Indian population-based cancer registries have reported a gradual rise in the ovarian cancer incidence over the years. Since ovary is composed of totipotent gametocytes and multipotent mesenchymal tissues, almost any type of tumor can arise from these tissues. Therefore, their proper recognition and classification is important for appropriate therapy and better prognosis.Aim: to look at the histopathological profile of various ovarian lesions in the local female subjects from central India.Methods: A prospective observational study was carried out on the surgically resected ovarian samples that were referred to the Pathology department over two and half year. A total of 100 ovarian cases were included. Histopathological examination of the specimen was done using standard protocols.Results: On gross examination, majority of non-neoplastic specimen showed unremarkable findings. Microscopic examination of non-neoplastic cases revealed that most of the cases were of follicular cyst followed by corpus luteum cyst. On the contrary, majority of neoplastic specimen showed cystic external surface on gross examination. Surface epithelial tumor was the most common histologic type amongst neoplastic cases. Most common histologic subtype amongst the surface epithelial tumors was found to be benign simple serous cystadenoma. Conclusion: In women from central India, commonest non-neoplastic lesion of ovary is follicular cyst whereas most common neoplastic lesion is surface epithelial tumor (benign simple serous cystadenoma).